Penerapan Metode SWOT-QSPM dalam Menentukan Strategi Pengembangan di CV. XYZ Kabupaten Sidoarjo - Sintya Tri Wahyuni; Dini Nafisatul Mutmainah; Rahmat Dhandy; Septine Brillyantina (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
CV. XYZ is an MSME in Sidoarjo Regency engaged in food processing, established in 2019 with dimsum skin as its main product. This study aims to formulate development strategies by applying the SWOT-QSPM method. The research uses a descriptive qualitative approach supported by quantitative analysis through IFE, EFE, SPACE, SWOT, and QSPM matrices. The SPACE Matrix analysis indicates that CV. XYZ is positioned in quadrant I, requiring an aggressive strategy by utilizing internal strengths to capture external opportunities. The SWOT analysis produces alternative strategies related to digital marketing expansion, retail partnerships, government collaboration, product innovation, packaging improvement, storage optimization, supplier diversification, and operational efficiency. The QSPM analysis identifies strengthening product branding through the establishment of a marketing team as the priority strategy with a Total Attractiveness Score of 6.48. The findings recommend structured marketing development and continuous evaluation to improve competitiveness, market expansion, and business sustainability